In Silico Analysis of Active Compounds in Brotowali (Tinospora crispa) as Antihyperglycemic Agents against α-Amylase Receptors - Mohammad Rofiq Usman; Ishrolana Lutfi Anggraeni; Caca Engellina; Imelda Eka Fitriananda; Wan Faizah; Faradibah Andarista (Indonesian Pharmacopeia Journal, 2025)
Hyperglycemia is a condition characterized by higher than normal blood sugar levels and is the main sign of diabetes mellitus. According to the International Diabetes Federation (IDF) in 2021, Indonesia ranks fifth with 19.47 million diabetics and a population of 179.72 million, and this makes the prevalence of diabetes in Indonesia 10.6%. One of the plants that is widely used as traditional medicine to reduce blood sugar levels is the brotowali plant (Tinospora crispa). This study aims to analyze the mechanism of active compounds of the brotowali plant (Tinospora crispa) that can inhibit the α-amylase enzyme through molecular tethering in silico. This study uses the method of tethering to receptors obtained from the PDB database (ID 1OSE). The positive control used was acarbose so as to obtain a new antihyperglycemic drug candidate with a good pharmacokinetic profile. The molecular tethering simulation results showed that the DL-Carnitine compound has the lowest ΔG value of -4.32 kcal/mol with a Ki value of 680.33 µM and a hydrophobic bond that plays an active role with the natural ligand ASP A:197. In terms of pharmacokinetics, the DL-carnitine compound is better than acarbose. It can be concluded that the DL-Carnitine compound is predicted to be carried out further as research as an antihyperglycemic candidate through α-amylase inhibition.